Rising Protectionism in US: Asia-Pacific’s Response - Rana, Pradumna B. (2018)
Asia-Pacific countries cannot influence decisions in the US, but they can pursue a three-pronged response that should enhance their resilience to possible global shocks generated by Trump’s protectionist policies.